2019
DOI: 10.1186/s13028-019-0449-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the shell gland and duodenum in relation to shell quality and bone strength in commercial laying hen hybrids

Abstract: BackgroundDuring the production period of laying hens, the number of cracked eggshells increases and the skeleton becomes brittle. Both these problems are related to ageing of the hen and cause economic problems for egg producers and impaired animal welfare. This study investigated key factors in the shell gland and duodenum related to eggshell quality and bone strength in laying hens during the production period. Five Lohmann Selected Leghorn (LSL) and five Lohmann Brown (LB), common hybrids in commercial egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 44 publications
2
11
1
Order By: Relevance
“…However, it is possible that some regeneration of structural bone occurred in the latter part of the production period, when egg production declined and days out of lay became more frequent. An improvement in tibial bone breaking strength during the production cycle has been observed in other studies (Leyendecker et al, 2005;Wistedt et al, 2019). 2004) concluded that the length of time that birds are in a continuously reproductive state is likely to be significant for degree of osteoporosis, and that short periods out of lay may allow regeneration of structural bone.…”
Section: Discussionsupporting
confidence: 58%
“…However, it is possible that some regeneration of structural bone occurred in the latter part of the production period, when egg production declined and days out of lay became more frequent. An improvement in tibial bone breaking strength during the production cycle has been observed in other studies (Leyendecker et al, 2005;Wistedt et al, 2019). 2004) concluded that the length of time that birds are in a continuously reproductive state is likely to be significant for degree of osteoporosis, and that short periods out of lay may allow regeneration of structural bone.…”
Section: Discussionsupporting
confidence: 58%
“…For female birds, such as layers, broilers, quails, and turkeys, the oviduct plays a more specific role in the breeding process. For example, the quality of the albumen and egg shell is mainly related to the function of magnum and uterine tissues, respectively ( Herrera et al., 2018 ; Wistedt et al., 2019 ). The decreasing efficiency of SSTs in UVJs caused by aging is regarded as another main factor affecting the decline of fertility rate in both breeders of layers and broilers ( Beaumont et al., 1992 ; Fasenko et al., 1992 ; Gumulka and Kapkowska, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The carbonate ion required for eggshell synthesis is catalyzed by carbonic anhydrases (CA), and uterine glandular cells possess the carbonic anhydrase activity sites. Growing evidence has demonstrated that high level of CA2 expression play a pivotal role for conversion of intracellular CO 2 to HCO 3 − in chicken [53,54]. As a member of the otopetrin gene family, OTOP2 gene may have similar functions to OTOP1, which regarded as modulator of cellular calcium in ux [55], to transport calcium across the uterine epithelium for eggshell calci cation [56].…”
Section: Discussionmentioning
confidence: 99%